Diagnosis of Lower Genital Tract Disease - Bottari, Fabio; Iacobone, Anna Daniela (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Lower genital tract diseases include vulvovaginal and HPV-related diseases, ranging from benign to pre-neoplastic and neoplastic lesions. Nowadays, there has been increasing interest in innovative methods to diagnose and prevent cervical cancer through HPV primary screening programs. However, other lower genital tract diseases are unrelated to HPV infection; hence, cytology, colposcopy, and sonography might play a crucial role in assessment and management. This Special Issue aims to address current and emerging issues in the field of the diagnosis, assessment, staging, and management of HPV-related and not-related pathology of the lower female anogenital tract. These may include new advancements in HPV testing and laboratory biomarkers, investigations on the actual role of cytology and implementation of diagnostic tools to implement differential diagnosis, and the current clinical management of lower genital tract diseases.